Language Barriers, Cultural Misalignment, and Workload Pressure: Unpacking Job Satisfaction Challenges Among Indonesian Nurses in Saudi Arabia: A Literature Review - Feby Saskiya Putri; Muh. Abdurrouf; Iwan Ardian; Dyah Wiji Puspita (Universitas Pahlawan Tuanku Tambusai, 2026)
Abstract Background: Job satisfaction among expatriate nurses is a critical issue in the global healthcare system, particularly in Saudi Arabia, where it is influenced by language barriers, cultural factors, and workload pressures. However, empirical evidence regarding the interrelationships among these three factors remains fragmented and lacks comprehensive integration. Objective: This literature review aims to integratively analyze the effects of language barriers, cultural factors, and workload on the job satisfaction of expatriate nurses, with a particular focus on Indonesian nurses working in Saudi Arabia. Methods: A systematic literature search was conducted across PubMed, ScienceDirect, SpringerLink, and DOAJ using the PRISMA 2020 approach. The search strategy employed combinations of keywords related to language barriers, cultural competence, workload, and job satisfaction. Inclusion criteria consisted of quantitative research articles with cross-sectional designs, involving nurse populations and relevant variables, published between 2021 and 2026. Of the 548 identified articles, 86 duplicates were removed and 462 articles were screened. A total of 12 articles met the inclusion criteria and were analyzed. Quality appraisal was performed using the Joanna Briggs Institute (JBI) tool. Results: High workload reduces job satisfaction through increased stress and burnout, while cultural factors and language barriers exert indirect effects through interaction quality and work-related pressure. Overall, expatriate nurses’ job satisfaction is influenced by the interplay of these three factors, highlighting the need for an integrative approach and a comprehensive conceptual model in managing multicultural nursing human resources. Keywords: Language Barriers, Cultural Competence, Workload, Job Satisfaction, Expatriate Nurses